Pembelajaran Matematika Berbasis Masalah di Kelas 4 Sekolah Dasar - Prastitasari, Herti; Prihandoko, Yogi; Jumadi, Jumadi; Sunarno, Sunarno (JKPD (Jurnal Kajian Pendidikan Dasar), 2024)
This article describes problem-based mathematics learning in elementary schools. The description begins with the concept of mathematics learning, the concept of problem-based learning and the steps of problem-based learning. The main part of this article is a discussion of problem-based learning in mathematics implemented in the fourth grade of SDN Antasan Besar 1 Banjarmasin. The implementation of the Problem-based learning model includes orientation to the problem, organizing students, guiding investigations, developing and presenting results and analyzing and evaluating the process and results of problem solving. Based on the results of the learning analysis carried out, it shows that problem-based mathematics learning goes well in elementary schools, problem-based mathematics learning can improve the quality of learning and improve student learning outcomes in elementary schools. Based on the results of the study, problem-based learning in mathematics is highly recommended in grade four elementary schools.